2008
DOI: 10.2298/mpns0804164m
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between C-reactive protein levels with leading risk factors for cardiovascular disease in men

Abstract: High sensitive CRP screening is useful in early detection and prevention of cardiovascular diseases

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
2
2
Order By: Relevance
“…The large positive correlation between Total:HDL cholesterol and medium positive correlation between LDL cholesterol and hsCRP was unexpected, and contrasts with previous research that found minimal or no correlation between these markers 75,76 except in children 77 …”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…The large positive correlation between Total:HDL cholesterol and medium positive correlation between LDL cholesterol and hsCRP was unexpected, and contrasts with previous research that found minimal or no correlation between these markers 75,76 except in children 77 …”
Section: Discussioncontrasting
confidence: 92%
“…The large positive correlation between Total:HDL cholesterol and medium positive correlation between LDL cholesterol and hsCRP was unexpected, and contrasts with previous research that found minimal or no correlation between these markers 75,76 except in children. 77 The medium negative correlation between hsCRP and HDL was also unexpected, as other studies have found no correlation between these two markers.…”
Section: Lipidscontrasting
confidence: 99%
See 1 more Smart Citation
“…The levels of blood plasma C-reactive protein (CRP) were characterized quantitatively by diffused light immunoturbidimetric method (Mirjanic-Azaric et al, 2008). The erythrocyte sedimentation rate (ESR) and the contents of blood plasma hemoglobin (Hb) of individual subjects were determined by the Westergen method (Cakal et al, 2009) and measured by an automated hematology analyzer, respectively.…”
Section: Other Clinical Measuresmentioning
confidence: 99%